Optimisation of sodium-cooled fast reactors proceedings of the international conference organized by the British Nuclear Energy Society in London, 28 November-1 December 1977. (British Nuclear Energy Society, 1978)
Sessions looked at the topics of safety, core, sub-assembly and fuel, overall design, sodium circuits and steam plant, and system benefit.